Penggunaan Citra Landsat 8 untuk Estimasi Kadar Khlorofil dan Hasil Tanaman Padi - I WAYAN NUARSA (Agrotrop : Journal on Agriculture Science, 2014)
The Use of Landsat 8 Imagery to Estimate Chlorophyl Content and Yield of Rice Plant.Predicting rice yield before harvest time is important to supporting planners and decision makers topredict the amount of rice that should be imported or exported and to enable governments to put inplace strategic contingency plans for the redistribution of food during times of famine. This study usedLandsat 8 that has better both spectral and radiometric resolution compared with the Landsat 7. Theresult of this study shows that using several Landsat 8 band as vegetation index provided better relationshipwith rice chlorophyll compared usind single band. Normalized Difference Vegetation Index (NDVI)has the best relationship with the chlorophyll content of rice plant compared with other vegetation indexand single band of Landsat 8 with the R2 of 0.936 . The form of relationship is linear with equation of y= 7.1043x + 0.0661, where y and x are chlorophyll content of rice plant and NDVI, respectively.Rice yield can be estimated in rice age approximatelly of 2 months with the equation of y = 30.495x2 -36.884x + 19.334, where y and x are rice yield in ton/ha and NDVI, respectively. The R² of thisestimation is 0.893 with the standard error of 0.372.